2011
DOI: 10.1099/jmm.0.030049-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR-based detection of Bordetella pertussis and Bordetella parapertussis in an Irish paediatric population

Abstract: Novel real-time PCR assays targeting the Bordetella pertussis insertion sequence IS481, the toxin promoter region and Bordetella parapertussis insertion sequence IS1001 were designed. PCR assays were capable of detecting ¡10 copies of target DNA per reaction, with an amplification efficiency of ¢90 %. From September 2003 to December 2009, per-nasal swabs and nasopharyngeal aspirates submitted for B. pertussis culture from patients ¡1 month to .15 years of age were examined by real-time PCR. Among 1324 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Thus, when PCR is compared to culture, the sensitivity of PCR is 100%. The sensitivity of culture compared to PCR ranges from 26% to 85% (93,150,(265)(266)(267)(268). It has been shown that the sensitivity of culture with regard to PCR sensitivity decreases with an increasing duration of disease, and thus shows a steeper decline than that of PCR (267).…”
Section: Factors That Influence the Sensitivity Of Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when PCR is compared to culture, the sensitivity of PCR is 100%. The sensitivity of culture compared to PCR ranges from 26% to 85% (93,150,(265)(266)(267)(268). It has been shown that the sensitivity of culture with regard to PCR sensitivity decreases with an increasing duration of disease, and thus shows a steeper decline than that of PCR (267).…”
Section: Factors That Influence the Sensitivity Of Diagnostic Methodsmentioning
confidence: 99%
“…The IS elements IS481 and IS1001 are the most used targets for detection of B. pertussis and B. parapertussis, respectively, by PCR (66,67). For simultaneous detection of B. pertussis and B. parapertussis, multiplex PCR assays targeting both IS elements have been developed (90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101).…”
Section: Pcr Assaysmentioning
confidence: 99%
“…In addition, two new sets of primers and Taqman probes were designed based on ptx promoter (PT-P) and B pertussis gene for a porin protein (BPTD_0837) (POR). The new ptx promoter assay was designed through modification of the primer and probe sequences described by Grogan et al (12) in an attempt to further improve the specificity of the assay. By aligning the genomes of several different Bordetella species, it was noted that the published probe sequence has only a single nucleotide mismatch with the corresponding sequences of B bronchiseptica and B parapertussis genome.…”
Section: Resultsmentioning
confidence: 99%
“…A single-target PCR, carefully designed to specifically and exclusively amplify B pertussis DNA would, therefore, be preferable to current assays based on IS 481 or multiple targets. Several real-time PCR assays designed to amplify non-IS 481 single-gene targets have been described for the specific detection of B pertussis (1214). In the present study, we evaluated the performance of these PCR assays in parallel with a novel real-time PCR assay that targets the B pertussis porin gene and the widely used IS 481 -based PCR assay.…”
mentioning
confidence: 99%
“…A mortalidade em lactentes é de aproximadamente 1% 10 . Entre os métodos diagnósticos laboratoriais mais utilizados, podemos citar a cultura de material de nasofaringe (método padrão, com alta sensibilidade, porém baixa especificidade), sorologias específicas (técnicas de ELISA, com baixa sensibilidade e especificidade) e reação em cadeia da polimerase (polymerase chain reaction, PCR), método atualmente mais utilizado, com alta especificidade (90%) e maior sensibilidade que a cultura convencional [11][12][13] . Dada a atual elevada incidência de coqueluche e seus variados modos de apresentação, este estudo tem como objetivo descrever as características demográficas e clínicas de pacientes pediátricos menores de 3 anos de idade internados em um hospital universitário terciário com diagnóstico de coqueluche confirmado por PCR no período de julho de 2011 a dezembro de 2012.…”
unclassified